Assessing the Causes of Dedicated Revenues\' Fractions in Health Care Centers and Strategies to Reduce Them (A Qualitative Study) - Jafarsadegh Tabrizi; Saeideh Alidoost; Ahmad Mardi; Mostafa Farshi-khorsand; Mohammadali Rahmat (بیمارستان, 2016)
Background: Lack of financial resources or their poor organization is one of the service delivery challenges and Fraction of dedicated revenues is significant problem in health centers in financial resources management. Hence, this study conducted to investigate causes of dedicated revenuechr('39')s fraction and strategies to reduce them.